Core Pluripotency Factors Directly Regulate Metabolism in Embryonic Stem Cell to Maintain Pluripotency. (23rd June 2015) - Kim, Hyunsoo; Jang, Hyonchol; Kim, Tae Wan; Kang, Byung‐Hee; Lee, Sang Eun; Jeon, Yoon Kyung; Chung, Doo Hyun; Choi, Jinmi; Shin, Jihoon; Cho, Eun‐Jung; Youn, Hong‐Duk
Abstract: Pluripotent stem cells (PSCs) have distinct metabolic properties that support their metabolic and energetic needs and affect their stemness. In particular, high glycolysis is critical for the generation and maintenance of PSCs. However, it is unknown how PSCs maintain and acquire this metabolic signature. In this study, we found that core pluripotency factors regulate glycolysis directly by controlling the expression of glycolytic enzymes. Specifically, Oct4 directly governs Hk2 and Pkm2, which are important glycolytic enzymes that determine the rate of glycolytic flux. The overexpression of Hk2 and Pkm2 sustains high levels of glycolysis during embryonic stem cell (ESC) differentiation. Moreover, the maintenance of high glycolysis levels by Hk2 and Pkm2 overexpression hampers differentiation and preserves the pluripotency of ESCs in the absence of leukemia inhibitory factor. Overall, our study identifies a direct molecular connection between core pluripotency factors and ESC metabolic signatures and demonstrates the significance of metabolism in cell fate determination. Stem Cells 2015;33:2699–2711 Abstract : Overexpression of Hk2 and Pkm2 enables ESCs to maintain high glycolytic flux. Sustaining high glycolytic flux during differentiation prevents ESCs from complete differentiation and allowing them to retain self‐renewal potential or pluripotency.